2016
DOI: 10.1080/00365521.2016.1224378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omeprazole or anti-reflux surgery on lower oesophageal sphincter characteristics and oesophageal acid exposure over 10 years

Abstract: Open ARS and OME were both effective in normalising acid reflux into the oesophagus even when studied over a period of 10 years. Anatomically and functionally the LOS was repaired durably by surgery, with increased resting pressure and abdominal length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Anti-reflux surgery is considered an effective treatment option for GERD and is widely performed in Western countries. Many clinical trials comparing anti-reflux surgery and PPI for GERD were conducted, and these trials found anti-reflux surgery as effective as or more effective than PPI at controlling GERD symptoms over a follow-up period of 5 years [87888990919293949596]. In addition, several studies among them demonstrated that anti-reflux surgery was likely to be cost-effective compared to medical treatment [909294].…”
Section: Resultsmentioning
confidence: 99%
“…Anti-reflux surgery is considered an effective treatment option for GERD and is widely performed in Western countries. Many clinical trials comparing anti-reflux surgery and PPI for GERD were conducted, and these trials found anti-reflux surgery as effective as or more effective than PPI at controlling GERD symptoms over a follow-up period of 5 years [87888990919293949596]. In addition, several studies among them demonstrated that anti-reflux surgery was likely to be cost-effective compared to medical treatment [909294].…”
Section: Resultsmentioning
confidence: 99%
“…These trials established that anti-reflux surgery is as effective as or more effective than PPI in controlling GERD symptoms over a follow-up period of 5 years. [250][251][252][253][254][255][256][257][258][259] Also, several studies demonstrated that anti-reflux surgery was likely to be cost-effective compared to medical treatment. 255,257,260 From the Statement 22: Anti-reflux surgery can be recommended as an alternative to proton pump inhibitor maintenance therapy to improve symptoms and quality of life in patients with proven gastroesophageal reflux disease.…”
Section: Anti-reflux Surgerymentioning
confidence: 99%
“…258 Moreover, several studies reported that anti-reflux surgery had a lower acid exposure of esophagus and higher pressure of LES than PPI treatment in short-term and long-term followup. 254,259,261 In terms of cost-effectiveness of the anti-reflux surgery, one study compared the cost-effectiveness of laparoscopic surgery (n = 155) and medical management (n = 104) using the data of a randomized multicenter trial. The results indicated that laparoscopic anti-reflux surgery is cost-effective, provided that its clinical benefits are sustained in the medium-to-long term.…”
Section: Anti-reflux Surgerymentioning
confidence: 99%
“…At short and medium follow-up, surgical treatment is more effective than medical management [5]; on the other hand, open anti-reflux surgery or the use of proton pump inhibitors (PPIs) are both effective in normalizing reflux into the esophagus in a follow-up of 10 years. Lower esophageal sphincter pressure is repaired and maintained after fundoplication [6]. b.…”
Section: Related To Outcomes [2 4]mentioning
confidence: 99%